Comparative study for novice engineering programmer: C++ vs VBA programming languages / Syarifah Adilah Mohamed Yusoff, Saiful Nizam Warris and Mohd Saifulnizam Abu Bakar - Mohamed Yusoff, Syarifah Adilah; Warris, Saiful Nizam; Abu Bakar, Mohd Saifulnizam (Unit Penerbitan JSKM, 2025)
The programming language significantly enhances students' problem-solving abilities; nonetheless, constructing a program is a complex endeavour due to insufficient metacognitive methods and the challenge of rectifying syntax errors. VBA and C++ are both programming languages that covers all the fundamental features for novice programmers such as concept of declaration, input and output process and basic structure of programming such as sequence, selection and repetition. Descriptive survey has been done to 29 students in Degree of Civil Engineering to investigate the usability and compared the functionality of both languages in the learning process which consist of background, learning difficulties, practical applications, user experience and final thoughts. The outcome reveals that students have been more convenient with VBA for practical, beginner experience, ease of use and understand the concept to real-world problem solving. This result could serve as benchmarking on how to teach programming in a way novice can comprehend, thinking and learning in their perspective of studies.